Transformation of Indonesian Migrant Workers’ Microenterprises in Kuala Lumpur: Implementation of Standard Operating Procedures and Quality Control as A Strategy to Improve Product Competitiveness - Pitaloka, Lola Kurnia; Kusumantoro; Melati, Inaya Sari; Farliana, Nina (Indonesian Journal of Devotion and Empowerment, 2025)
This community engagement program aimed to enhance the capacity of Indonesian migrant workers’ microenterprises in Kuala Lumpur through training and implementation of Standard Operating Procedures (SOP) and Quality Control (QC). Based on a preliminary survey, most business owners lacked fundamental skills in production management and quality control, resulting in inconsistent product quality. The program was conducted on May 18, 2025, involving 35 microenterprise participants. Activities included theoretical training and practical simulations on SOP development and QC application. Evaluation was carried out through pre-tests and post-tests, which revealed a significant improvement in the participants' average score from 45.25 to 83.75, with the most notable increase observed in the ability to draft QC guidelines. The results demonstrated that the application of SOP and QC can effectively improve product consistency, quality, and competitiveness. However, challenges remained in the implementation process, such as time constraints, limited equipment, and low technical literacy. Therefore, follow-up strategies such as ongoing mentorship, the use of visual SOPs, and the establishment of peer learning communities are essential to ensure sustainability.